Hyperspectral dimension reduction and navel orange surface disease defect classification using independent component analysis-genetic algorithm - Li, Jing; He, Liang; Liu, Muhua; Chen, Jinyin; Xue, Long (Frontiers in Nutrition, 2022)
Canker is a common disease of navel oranges that is visible before harvest, and penicilliosis is a common disease occurring after harvest and storage. In this research, the typical fruit surface, canker spots, penicillium spore and hypha of navel oranges were respectively identified by hyperspectral imaging. First, the light intensity on the edge of samples in hyperspectral images was improved by spherical correction. Then, independent component images and weight coefficients were obtained using independent component analysis. This approach, combined with use of a genetic algorithm, was used to select six characteristic wavelengths. The method achieved dimension reduction of hyperspectral data, and the testing time was reduced from 46.21 s to 1.26 s for a self-developed online detection system. Finally, a deep learning neural network model was established, and the four kinds of surface pixels were identified accurately.